2020
DOI: 10.7554/elife.56630
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific roles for AKT in affective behavior, spatial memory, and extinction related to psychiatric disorders

Abstract: AKT is implicated in neurological disorders. AKT has three isoforms, AKT1/AKT2/AKT3, with brain cell type-specific expression that may differentially influence behavior. Therefore, we examined single Akt isoform, conditional brain-specific Akt1, and double Akt1/3 mutant mice in behaviors relevant to neuropsychiatric disorders. Because sex is a determinant of these disorders but poorly understood, sex was an experimental variable in our design. Our studies revealed AKT isoform- and sex-specific effects on anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 107 publications
1
30
0
Order By: Relevance
“…2017 ), and we demonstrated previously that Akt3 KO mice have normal synaptic plasticity in the hippocampus ( Levenga et al. 2017 ; Wong et al. 2020 ).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…2017 ), and we demonstrated previously that Akt3 KO mice have normal synaptic plasticity in the hippocampus ( Levenga et al. 2017 ; Wong et al. 2020 ).…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, we found that AKT1 can compensate for the loss of AKT3 activity to mediate normal expression of metabotropic glutamate receptor-dependent long-term depression in the hippocampus ( Levenga et al. 2017 ) and normal memory ( Wong et al. 2020 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is intriguing that females had higher levels of Akt phosphoproteins than males in the DG, which adds to the literature showing greater Akt phosphoproteins in the brain (26,48) and periphery (46) of females compared to males. The Akt pathway provides a mechanism through which extrinsic factors such as neurotrophic factors can activate transcription factors to affect the regulation of neural stem cells and neurogenesis in the DG (49).…”
Section: Sex Differences In Mapk and Akt Cell Signalling Pathways In The Dgmentioning
confidence: 59%
“…AKT1 are one of them, and that lack of AKT1 increases the behavior of anxiety in mice. However, restoring the expression of AKT1 in the prefrontal cortex (PFC) can improve fear memory, behavior, where the GAGB pathway mediated this process (40). In addition to playing an important role in synaptic transmission, memory, and psychosis, AKT is also one of the most common highly activated protein kinases in human cancer.…”
Section: Figure 1 Depicts the Drug-component-target Relationshipsmentioning
confidence: 99%